Study of the Parameters of The Blood Hemostasis System in Patients with Chronic Obstructive Pulmonary Disease - Sh.M Ibatova; F.Kh.Mamatkulova (Genius Journals, 2023)
It is known that the lungs play a significant role in maintaining the physiological balance of the coagulation, fibrinolytic system and in the regulation of hemostasis. We examined 100 patients with chronic obstructive pulmonary disease, who were divided into two groups: group I consisted of 30 patients aged 12-14 years (with bronchial deformation - 24 patients; with bronchiectasis - 6), group II - 70 patients aged 15 - 16 years (with bronchial deformation - 46 patients; with bronchiectasis - 24). An analysis of the parameters of the blood hemostasis system in patients with chronic obstructive pulmonary disease was performed. The data presented highlight the significant pathogenetic significance of changes in hemostasis in patients with chronic obstructive pulmonary disease, which requires the search for new methods of pathogenetic therapy based on anticoagulant effects.
Keywords: Chronic obstructive pulmonary disease; patients; blood